Determinación de variables de cálculo para la optimización del proceso de conminución en la Planta de Beneficio Mineral Reina del Cisne II. El Pache. Cantón Portovelo. Provincia de El Oro. - Valarezo Riofrío, Jorge Michael (2023)
This work identifies and quantitatively determines all the calculation variables for comminution processes, understood as crushing and grinding. Two phases are presented and technically described: 1) description of the raw material to be processed and the flow chart with all the comminution equipment involved for the present case; and, 2) the identification and calculation of variables such as: reduction degrees, grip angle, rotation, tonnage and energy consumption for crushers; and, reduction, rotation frequency, critical rotation fraction, filling degree, energy consumed, motor power and flow for mills. The comminution processes in the Beneficiation Plants of the El Pache sector in Portovelo Ecuador are basically analyzed, with emphasis on the Reina del Cisne II Beneficiation Plant with an installed capacity of 120 TPD. Information from plants such as Alto Vizcaya and Ecometals will be considered for the analysis and final comparisons for improvement and optimization of comminution processes. The results obtained establish that the operating costs of a concentration plant are directly related to the period of time it is operated, its income - expenditure, profit and energy consumption in its mills (kw.h/ton material). Technologically, the sequence of crushing equipment: primary jaws - secondary jaws; jaws - cones; are for hard and abrasive rock such as andesite with strengths above 120 MPa and work index of 12.3 kWh/ton. Working with ball mills in closed circuits allows an improvement in reduction rates and energy consumption. Rittinger, Taggart, Lewenson and Bond principles should be applied to understand optimum reduction grades, energy consumed and motor power at full load to verify overall plant savings of 1 to 5% per ton of material processed. Key words: Comminution. Rotation frequency. Energy consumption.